ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA PEMBELAJARAN DARING BERBANTUAN WHATSAPP SELAMA MASA PANDEMI COVID-19 - Vany Diah Puspitasari; Jayanti Putri Purwaningrum; Ratri Rahayu (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2021)
The purpose of this study was to analyze mathematical communication skills in online learning of the Two Variable Linear Equation System (SPLDV) material with Whatsapp assistance during the Covid-19 pandemic in grade VIII SMP 3 Bae. This research is a qualitative descriptive study conducted in class VIII-E SMP 3 Bae Kudus with 28 students as research subjects. This mathematical communication ability is grouped into 3 criteria, namely high, medium, and low, each criterion is taken by 3 students to conduct an interview test. Data collection was taken through interviews and tests of mathematical communication skills, while data analysis began by examining all available data from various sources, namely the written test results of mathematical communication skills and the results of interviews. Based on the research, it was found that out of 28 students there were 3 students who had high communication skills, 4 students had moderate communication skills, and 21 students had moderate abilities.